Judges’ Considerations in Deciding Mangrove Timber Smuggling Cases - Ramadhani, Deaf Wahyuni (Universitas Kuningan, 2023)
Mangrove forests in Indonesia constitute 23% of the world’s mangrove ecosystem. This has an impact on the high rate of mangrove production in Indonesia, which triggers export smuggling. In fact, the prohibition on export smuggling has been regulated in Article 102A letter e of the Customs Law. Accordingly, this study aims to analyze the judges’ considerations in deciding mangrove export smuggling cases. This doctrinal legal research applied a case approach and used secondary data obtained from library materials through literature study. The collected data were then analyzed deductively. Analysis of the verdict on mangrove export smuggling cases found that the judges’ considerations had paid attention to the preservation of natural resources but were not yet oriented towards the preservation of the mangrove ecosystem, and the penalties applied were still minimal.